Novel Buck-Boost PFC Converter with Three-State Switching Cell - Morais, Douglas Carvalho [UNESP]; Jose Mendes De Seixas, Falcondes [UNESP]; De Oro Arenas, Luis [UNESP]; Carvalho Souza, Lucas [UNESP]; De Souza Da Costa E Silva, Luciano (Institute of Electrical and Electronics Engineers (IEEE), 2019)
In this paper, a buck-boost converter with power factor correction is proposed, using a three-state switching cell named of B configuration, operating in continuous conduction mode. The type B cell insertion on the buck-boost converter keeps conventional structure statistic characteristics and brings as advantage, stress current division in all semiconductors by half inductor current. Moreover, the ripple frequency on converter energy storage elements will be twice switching frequency value, making easier the design of input and output passive filters and reducing the converter final volume and weight. Preliminary simulation results prove the converter effectiveness on power factor correction, keeping output voltage stable in a specified operation point, with a total harmonic distortion of input current below 1.5%.
Keywords: buck-boost converter; continuous conduction mode; power factor correction; three-state switching cell; total harmonic distortion